Twarze współczesnego człowieka - Diament, Janusz (Społeczeństwo, 2022)
What is your face in light of Christ? John Paul II could ask any of us such a question, if after forty years from the first pilgrimage to his fatherland he decided to start another apostolic travel to Poland. What would be the current reply of men? Would we be afraid of Christ looking through our hearts? How much of the teachings of the Polish pope is still in us, what is the „Restored face of this soil?”. The first visit of the Polish pope, 40 years ago, on 2 June 1979, which greatly contributed to the beginning of the downfall of communism, evoked indescribable enthusiasm in Poland and major reservations of the authorities. Next pilgrimages also had played their role in the shaping of moral attitude in the society, which later on was also visible in the social teachings of the whole Church.